Sistemas de cultivo em área de reforma de cana-de-açúcar e a sucessão de culturas na composição da comunidade infestante - Soares, Maria Beatriz Bernardes [UNESP] (2014)
The renewal of plantations is important to maintain high agricultural productivity of the culture of sugarcane and is usually performed after five harvests,so the aim of this study was to evaluate the influence of cropping systems and crops used in succession in the composition of the weed community in areas of reform raw cane.This study was carried out on Acrisol eutrophic soil, located in the city of Novais, São Paulo, insugar cane harvested without prior burning in the last five years. The experiment was conducted in a completelyrandomized design, using a splitplot arrangement with four replications. The main treatments consisted of three cropping systems: conventional, minimum tillage and no-tillage. Secondary treatments were three commercial oilseed crops: peanut, sunflower and soybean, two choices of green manure: sunnhemp and velvet bean, plus a fallow plot. After 180 days of harvest of sugar cane, the number of weeds.m-2was counted and determined the dry mass of shoots, then calculating their phytosociological index. Among the management systems of soil, the no tillage system showed a suppressive effect of weeds, resulting in fewer plants, less dry mass of plants and less variety of species, suppressing species that are considered important in the sugarcane crop. The use of legumes such as soybean, groundnut and green manure in rotation with sugarcane in these areas of reform was beneficial, controlling the population of invasive plants. The combination of these two factors can be considered favorable because besides decreasing the number and dry weight of weed plants per unit area, also downplayed the importance of the species considered problematic. Sunflower growing under the conditions studied, was not effective in controlling the weed population